HUMOR USED IN MARK WATER'S MOVIE "MEAN GIRLS" - Samahendra, Yusril -; Halim, Abdul (ELITERATE : Journal of English Linguistics and Literature Studies, 2023)
In this research study, the researcher aims to find out the use of humor by the characters in the movie "Mean Girls." In this study, researchers examined the types and functions of the use of humor by the characters in the film "Mean Girls." In examining the types of humor, researchers used Martin's theory (2007) and for the use of humor function researchers used Attardo's theory (1994). Descriptive qualitative method was used in this research, in which the researcher watched the film, observed, analyzed the data and compiled then drew conclusions. The researcher found that the characters in the movie "Mean Girls" use all types of humor in 34 extracts. Jokes, spontaneous conversational humor, and unintentional humor can be found in this movie, where all the uses of humor have different functions and are in accordance with the conditions of the characters when using the humor. All 4 functions of humor are used by the characters found in the movie. Social management is used by the characters in this movie to intimidate other characters, strengthen bonds between characters, and appear more dominant than other characters. For the function of humor decommitment, the characters in this movie use humor to reduce uncomfortable or awkward situations. As For the function of humor mediation, the characters in "Mean Girls" used humor to avoid things that made it possible to embarrass themselves and avoid problems with other characters. As well as the function of humor defunctionalization, the characters in this movie used humor to play with words to create new meanings.Keywords: Humor, Movie.